Comparative Effectiveness of Sunnah Fasting Variations on Fasting Blood Glucose Monitoring in Type 2 Diabetes Mellitus: A Pragmatic Pilot Study - Rosyid, Abdur; Satibi, Satibi; Rahmawati, Fita; Lazuardi, Lutfan (Sciences of Pharmacy, 2026)
Intermittent fasting has increasingly been incorporated into complementary and alternative medicine (CAM) strategies for the management of type 2 diabetes mellitus (T2DM). The extent to which weekly fasting frequency dictates glycemic outcomes is well-noted; however, the distinct clinical benefit of increasing Sunnah fasting adherence to two days weekly remains an unresolved question in diabetes management. This study aims to compare the effectiveness of Monday-only Sunnah fasting versus combined Monday and Thursday Sunnah fasting on Fasting Blood Glucose (FBG) among patients with Type 2 Diabetes Mellitus (T2DM). This research is a pre-experimental employing a within-subject exploratory pilot comparison with a single-group pre-post design involving 50 participants selected through purposive sampling, with data analyzed using the Wilcoxon Signed Ranks Test (p < 0.05). The results demonstrated that most participants (84%) were between 43 and 54 years of age, and the majority were female (56%). practicing Sunnah fasting twice weekly (Monday and Thursday) resulted in significantly lower average FBG (186,67 mg/dL) compared to fasting only once a week on Mondays (202.28 mg/dL), statistically significant reduction in FBG (Z= -2.660, p= 0.008; r= 0.37, Cohen’s d= 0.79). The study suggests that practicing Sunnah fasting twice weekly offers a more favorable impact on fasting blood glucose control for T2DM patients than fasting only once a week.